2016
DOI: 10.1186/s12913-016-1660-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of China’s New Rural Cooperative Medical Scheme on reducing medical impoverishment in rural Yanbian: An alternative approach

Abstract: BackgroudThis study aimed to measure the poverty head count ratio and poverty gap of rural Yanbian in order to examine whether China’s New Rural Cooperative Medical Scheme has alleviated its medical impoverishment and to compare the results of this alternative approach with those of a World Bank approach.MethodsThis cross-sectional study was based on a stratified random sample survey of 1,987 households and 6,135 individuals conducted in 2008 across eight counties in Yanbian Korean Autonomous Prefecture, Jilin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Furthermore, a recent study based on a national sample of rural residents from the 2011–2012 wave of China Health and Retirement Longitudinal Study (CHARLS) has shown that the coverage of NCMS associated with less delayed inpatient care [ 11 ]. Sun and his co-workers have recently demonstrated that the NCMS reduced the number of medically impoverished households by 24.6% in Yanbian [ 12 ]. Rural residents have greatly benefited from the implementation of the NCMS [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a recent study based on a national sample of rural residents from the 2011–2012 wave of China Health and Retirement Longitudinal Study (CHARLS) has shown that the coverage of NCMS associated with less delayed inpatient care [ 11 ]. Sun and his co-workers have recently demonstrated that the NCMS reduced the number of medically impoverished households by 24.6% in Yanbian [ 12 ]. Rural residents have greatly benefited from the implementation of the NCMS [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It indicated that economically affluent groups in the urban were more likely to receive advantageous finance reimbursements policy from independent insurance system, and meantime the reimbursements were also higher [ 21 ]. One study also showed that the implementation of essential medicines policies on primary healthcare institutions has certain positive but limited effects [ 22 ], which indicated that severe illness and impoverishment still occur like the twins in rural area [ 23 ]. Meanwhile, there were remarked difference in postoperative inflammation reaction among different medical insurance type only for mitral valve population but not for ASD occlusion population.…”
Section: Discussionmentioning
confidence: 99%
“…For rural patients, the medicine expenditure was found to have a negative impact on community clinic visits. By 2014, the reimbursement rate was only 60% for expenses for community health services in rural areas, meaning that medical care was a heavy economic burden [31].…”
Section: Discussionmentioning
confidence: 99%